2018
DOI: 10.1111/cns.12789
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral fragmentation in the D1CT‐7 mouse model of Tourette's syndrome

Abstract: The results of this study show that the D1CT-7 mouse model is subjected to a behavioral fragmentation, with repercussions going beyond the simple tic-like phenomenon. These phenotypes are strikingly akin to behavioral problems observed in patients with TS and further validate the power of this model in summarizing pivotal behavioral aspects of TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…T-patterns are widely and advantageously used in numerous research areas and they can offer very useful results in studies involving both human and animal subjects. For example, using TPA, it is possible to study neuropsychiatric diseases [19][20][21][22], route-tracing stereotypies in mice [23], the interactions between humans and animals [24] or between humans and artificial agents [25], interactions between hormones and behavior [26], feeding behavior in rodents [27], and the behavior in a model of Tourette's syndrome [28] and in a model of Parkinson's disease [29]; TPA has been used also to study movement and behavioral disorders mainly in human subjects but also in animals [30]. Finally, and importantly, with numerous studies available, T-pattern analysis has demonstrated its usefulness and affordability also in the study of rodent anxiety and anxiety-related behaviors [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…T-patterns are widely and advantageously used in numerous research areas and they can offer very useful results in studies involving both human and animal subjects. For example, using TPA, it is possible to study neuropsychiatric diseases [19][20][21][22], route-tracing stereotypies in mice [23], the interactions between humans and animals [24] or between humans and artificial agents [25], interactions between hormones and behavior [26], feeding behavior in rodents [27], and the behavior in a model of Tourette's syndrome [28] and in a model of Parkinson's disease [29]; TPA has been used also to study movement and behavioral disorders mainly in human subjects but also in animals [30]. Finally, and importantly, with numerous studies available, T-pattern analysis has demonstrated its usefulness and affordability also in the study of rodent anxiety and anxiety-related behaviors [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Another important novelty of the present study was the employment of Matrix and T-pattern analyses to deeply investigate the effect of DHT on the dynamics of sexual behavior. Indeed, even though such methodologies are considered valuable tools for behavioural testing in rodent models (Casarrubea et al, 2018;Santangelo et al, 2018), they have never been applied in studies focusing on sexuality. Interestingly, Matrix and T-pattern analyses were able to reveal several analogies and some divergences in the sexual behavior dynamics observed after EB + DHT or EB + P administration.…”
Section: Discussionmentioning
confidence: 99%
“…The stereotyped behavior of the mice was recorded according to the scoring criteria reported previously ( Santangelo et al, 2018 ). Through a transparent box (35 cm length × 25 cm width × 25 cm height), spontaneous motor behavior and the number of Head-Body Twitch (the HBT number) ( Chen et al, 2019 ) were used to evaluate the tic-like behavior of the mice.…”
Section: Methodsmentioning
confidence: 99%